Modelo de negocio para la puesta en valor del turismo gastronómico en el cantón Portoviejo- Ecuador - Alcívar Loor, Erika Yulissa (2023)
The purpose of this research work was the proposal to design a business model for the enhancement of gastronomic tourism in the Portoviejo canton, in which through a methodological design of a non-experimental exploratory nature assisted by the deductive and analytical-synthetic method with a quantitative and qualitative approach; It consists of three methodological phases: in the first phase, a situational diagnosis of gastronomic tourism businesses was developed, through bibliographic review and field work, the characterization and delimitation of the study area was obtained, identifying the restaurants with the highest score based on the criteria of the visitors, the most scored on the TripAdvisor platform and those of category two and three according to MINTUR. In the second phase, the study of supply and demand was carried out, applying interviews to the owners and managers of the selected restaurants, in addition to 196 surveys of tourists, identifying that one of the main travel motivations is gastronomic diversity. Local, these results allowed the elaboration of the strategic SWOT. Finally, the third phase consisted of the business model using the CANVAS method, identifying the most appropriate strategies for the enhancement of gastronomic tourism. The purpose of the investigation is that the restaurants of the Portoviejo canton can use a business model for the enhancement and that allows them to define the offer of their products and services in order to expand the market segment.